The dependence of alpha-tocopheroxyl radical reduction by hydroxy-2,3-diarylxanthones on structure and micro-environment - Morlière, Patrice (2012)
The flavonoid quercetin is known to reduce the α-tocopheroxyl radical (˙TocO) and reconstitute α-tocopherol (TocOH). Structurally related polyphenolic compounds, hydroxy-2,3-diarylxanthones (XH), exhibit antioxidant activity which exceeds that of quercetin in biological systems. In the present study repair of ˙TocO by a series of these XH has been evaluated using pulse radiolysis. It has been shown that, among the studied XH, only 2,3-bis(3,4-dihydroxyphenyl)-9H-xanthen-9-one (XH9) reduces ˙TocO, though repair depends strongly on the micro-environment. In cationic cetyltrimethylammonium bromide (CTAB) micelles, 30% of ˙TocO radicals are repaired at a rate constant of ∼7.4 × 106 M−1 s−1 by XH9 compared to 1.7 × 107 M−1 s−1 by ascorbate. Water-soluble Trolox (TrOH) radicals (˙TrO) are restored by XH9 in CTAB (rate constant ∼3 × 104 M−1 s−1) but not in neutral TX100 micelles where only 15% of ˙TocO are repaired (rate constant ∼4.5 × 105 M−1 s−1). In basic aqueous solutions ˙TrO is readily reduced by deprotonated XH9 species leading to ionized XH9 radical species (radical pKa ∼10). An equilibrium is observed (K = 130) yielding an estimate of 130 mV for the reduction potential of the [˙X9,H+/XH9] couple at pH 11, lower than the 250 mV for the [˙TrO,H+/TrOH] couple. A comparable value (100 mV) has been determined by cyclic voltammetry measurements.